Percepção dos serviços ecossistêmicos da infraestrutura verde do Parque Parreão I, Fortaleza-CE, na abordagem salutogênica em saúde - Mesquita, Emanuel Portela de (2022)
In the perspective of understanding the benefits provided to individuals by a green area within cities with high levels of urbanization and territorial occupation, such as Fortaleza, identifying ecosystem services and how these reverberate in well-being and quality of life, this paper presents and discusses results of a research conducted in the Parreão I Park. To understand the benefits offered by the green infrastructure of the Parreão I Park, in Regional 4 of the city of Fortaleza, Ceará, to the individuals who frequent it. The research was exploratory, using a qualitative approach. The place chosen for the study was Parreão I Park, located between the neighborhoods Parreão and Fátima. Parreão I Park was chosen as the target for the research because it is a park that encompasses several elements that have been important in the historical evolution of urban parks in the city. A questionnaire was applied relating ecosystem services to green and blue urban infrastructure according to CICES v5.1. This questionnaire sought personal information, ways of using the park, identify provisioning, regulation and maintenance services, cultural services and personal sensations. In all, 100 people of both genders were interviewed, ranging in age from 18 to over 80 years old, with high school to college education. Around 50% of the interviewees lived in neighborhoods near the park and frequented it mainly for sports, recreation and leisure activities, more than three times a week. Among the functions of the park, it stands out as a place for recreation and landscape contemplation. All the interviewees highlighted that the park improves the temperature and offers habitat for living beings and most of them that it reduces air pollution, noise and helps the cycling of nutrients. Among the ecosystem services people mainly responded that the park is very useful as an educational medium, as a way to discover and experience nature, as well as to spend time with family and friends in order to relax and escape from city life. Being located in a region of intense socioeconomic activity in the city of Fortaleza, and of great flux of people, whose processes of production, consumption and provision of services still follow, above all, the economic logic, expressed through significant impacts for environmental degradation, the Parreão I Park gains expressiveness particularly by the continuous and significant increase of anthropic pressure suffered, due to population densification in the city and in its surroundings, putting at risk the preservation of plant and animal specimens. The analysis of the questionnaires applied points to a full agreement, by the interviewed visitors, about the park's ability to mitigate air pollution, climate improvements, noise mitigation and habitat for plants and animals.